PERILAKU MENGAKSES PORNOGRAFI PADA ANAK USIA SEKOLAH DASAR (7-12 TAHUN) (Studi Kasus di Rumah Pintar Bangjo Semarang) - Fathimah Az Zahrah; Syamsul Huda BM; Ratih Indraswari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The development of technology especially the internet leads to access pornographic content more easily. the fact says that the intensity of access of pornography via the internet in Semarang is very high.The target of pornography industry, this time has increased into elementary school children with average accesor pornography are 11 years old. This research aimed to review more about pornography access behavior of children in elemantary school in Semarang. This qualitative research used descriptive approach, by using snowball sampling technique got 7 informants (elementary school age) lived in the area around Rumah Pintar Semarang. Data collection is done by in depth interview. Data validation is done by using triangulation to 4 informants.The result showed that the youngest informant (6 years old) got influenced by pornography contents. Kind of the media such as naked photo of people, porn photo or video, kissing, masturbation video, sexual interraction, and Indonesian horror movie which shown some sexual scenes. The impact of accessing phornograpy has reached decentralisation level where the contents has been considered as an usual thing for children. They got internet access by buying a package once in a month about Rp. 20,000 – 60,000, WiFi network provided in Sanggar Hani, and Warnet that the visited in holiday. Informants got these contents from social media (Facebook, Instagram, etc), search engine (XXX, Bokep, BF Indonesia, Satpam Kurang Ajar), applications, game advertisements, GTA and war games, and some channels in television. Informants has been also done sexual experiments through kids game or thought by adult.